New type of the unique continuation property for a fractional diffusion equation and an inverse source problem - Wenyi Liu; Chengbin Du; Zhiyuan Li (Boundary Value Problems, 2024)
Abstract In this work, a new type of the unique continuation property for time-fractional diffusion equations is studied. The proof is mainly based on the Laplace transform and the properties of Bessel functions. As an application, the uniqueness of the inverse problem in the simultaneous determination of spatially dependent source terms and fractional order from sparse boundary observation data is established.